Literary Theory and Literature Education in Finnish Upper Secondary School: A Historical Survey - Mäkikalli Aino (Univerzita Karlova, Filozofická fakulta Praha, 2025)
This article examines how literature education has changed in Finnish upper secondary school and what kind of theoretical background assumptions are made in the processing of literature. Early on, the aim of teaching literature in Finnish upper secondary schools was to emphasize national identity. Literary works about Finnish people were considered the strength of the young nation. The teaching of literature focused on learning national literature, and on knowing the authors and their works. From the 1950s onwards, new criticism influenced the teaching of literature, and close reading became the key tool for approaching literature. Gradually, the teaching of literature expanded from national literature to young adults’ literature, popular literature, and contemporary literature. In the 1980s, various literary approaches and background theories were emphasized in the learning materials. However, current literary teaching is still tied to new critical and formalistic theory. At the end of the article, the question is asked whether it would be necessary to change this approach so that literature would continue to attract young readers.